The customers’ satisfaction towards service quality of Out Going Inspection (OGI) at UMW Advantech Sdn Bhd/ Norahayu Nordin - Nordin, Norahayu (Faculty of Business and Management, 2011)
This first chapter is an overview of the research study that discussed the background of the study, background of organization, problem statement stating the problem of customers’ satisfaction towards Out Going Inspection (OGI) at UMW Advantech, the research objective and research question which the researcher has to answer through his finding, significance of the study, scope of study and the limitations of the study in doing this project paper. In addition, to understand readers better with this study, definition of term and organization of the study are also included. In chapter two, the researcher will include the literature review, which are the past research that purposely use to support the researcher theoretical framework. The theoretical framework which the researcher has to construct to find the answer to the research question and research objective. The independent variable, which the researcher identifies five (5) dimension (tangible, reliability, responsiveness, assurance and empathy) that have a relationship with customers’ satisfaction towards Outgoing Inspection (OGI) by UASB. Meanwhile, in chapter three the researcher will include methodology that of the procedure employed in order to achieve the objective of the study and the researcher is required to state the procedure to attain data from primary data or secondary data. The primary data include questionnaire. The secondary data are required data from other sources such as internal data and secondary data which are publish by another researcher.